Efektivitas Terapi SEFT (Spiritual Emotional Freedom Technique) Terhadap Intensitas Merokok Prajurit Batalyon Kavaleri 7 / Pasukan Serbu Khusus Jakarta Timur Tahun 2019 - Dwi Septian Wijaya (Celebes Health Journal, 2019)
Smoking is one of the habits carried out by most people, including teenagers. This study aims to determine the effectiveness of SEFT therapy on the intensity of smoking prajurti 7 cavalry battalion / special assault troop’s jaya Kodam East Jakarta. The design of the study used Quasi Experiments with the pretest - posttest design with control group design approach. The samples in the study of 18 intervention groups and 18 control groups. Data analysis using Repeated Anova and Friedman test. Based on the results of the analysis with the Friedman test shows the p-value of 0,000 in the intervention group, so it can be said that there is a very significant difference. Then in the control group the p-value is 0.201, so that it can be said that there is no significant difference. The conclusion SEFT therapy proved effective in reducing the intensity of smoking